DOZ047.69: Tracking outcomes of tracheoesophageal fistula and esophageal atresia in pediatric population. (24th June 2019) - Sharma, I; Thaker, S; Jensen, T; Finck, C
Abstract: Purpose: The purpose of this study is to conduct a retrospective chart review of patients with a rare congenital deformity, tracheoesophageal fistula, and esophageal atresia treated at a small, freestanding Children's Hospital. The goal is to identify important variables to inform clinical pathways and prospective database creation. Current national surgical quality databases do not track tracheoesophageal fistula/esophageal atresia (TEF/EA)-specific data points such as TEF-type and incidence of postoperative complications such as gastroesophageal reflux disease (GERD) and esophageal stricture. Methods: Patients diagnosed with esophageal atresia and trachesophageal fistula between January 2005 and January 2019 were identified using the appropriate ICD 9 or ICD 10 codes. Data for 35 variables including patient demographics and type of esophageal atresia were abstracted. SPSS 16.0 software was used for descriptive statistics. Results: A total of 43 patients were identified, 64.3% female and 35.7% male. 77.5% were type C, 12.5% type A, 7.5% type H, and 2.5% type D. 15% were long-gap type. 53.8% had postoperative esophageal strictures, and 66.7% had postoperative gastroesophageal reflux disease. Of those who had strictures, 77.2% of patients required at least three postoperative dilations for stricture, with an overall mean six dilations. 26.2% of patients had tracheomalacia; of these, two patients underwent thoracoscopic aortopexy. Four patients were not included in subgroup analysis: two patients had missing variables, one patient passed away before surgical intervention, and one patient has not yet undergone surgical intervention for EA/TEF. Conclusions: We conclude that, although a rare congenital anomaly, a database dedicated to tracheoesophageal fistula and esophageal atresia at a pediatric hospital can aid in reviewing trends in outcomes and inform standardization of management.